PENINGKATAN KOMPETENSI PEDAGOGIK GURU PRODUKTIF DALAM MENYUSUN RENCANA PELAKSANAAN PEMBELAJARAN (RPP) MELALUI IN HOUSE TRAINING (IHT) DI SDN 09 SUNGAI LIMAU - Yuliarni Yuliarni (STKIP Pesisir Selatan, 2017)
ABSTRACTBased on the results of observations and supervision conducted by the authors showed that the pedagogic competence of teachers in preparing the RPP is still low. The purpose of this study is to describe and obtain information about the improvement of pedagogic competence of productive teachers in preparing the Learning Implementation Plan (RPP) through In House Training (IHT) at SDN 09 Sungai Limau. This study is a school action research. The research procedures in this study include planning, action, obeservation and reflection. This study consists of two cycles with four meetings. The subjects consisted of 6 productive teachers teaching at SDN 09 Sungai Limau. The data were collected using obeservation sheets. Data were analyzed using percentages. The results showed that the implementation of In House Training (IHT) can improve the pedagogic competence of teachers in preparing the RPP. This is evidenced by the average value of the initial competence of teachers before the program is 74. Then after IHT activities there is an increase in cycle I is 78.70 (good) and after that increases in cycle II to 87.56 (very good).Keywords: Pedagogic Competency, IHT, RPPABSTRACTBased on the results of observations and supervision conducted by the authors showed that the pedagogic competence of teachers in preparing the RPP is still low. The purpose of this study is to describe and obtain information about the improvement of pedagogic competence of productive teachers in preparing the Learning Implementation Plan (RPP) through In House Training (IHT) at SDN 09 Sungai Limau. This study is a school action research. The research procedures in this study include planning, action, obeservation and reflection. This study consists of two cycles with four meetings. The subjects consisted of 6 productive teachers teaching at SDN 09 Sungai Limau. The data were collected using obeservation sheets. Data were analyzed using percentages. The results showed that the implementation of In House Training (IHT) can improve the pedagogic competence of teachers in preparing the RPP. This is evidenced by the average value of the initial competence of teachers before the program is 74. Then after IHT activities there is an increase in cycle I is 78.70 (good) and after that increases in cycle II to 87.56 (very good).Keywords: Pedagogic Competency, IHT, RPP